ANALYSIS OF SYARIAH COMPLIANCE FINANCING AT PT BANK SUMUT SHARIA BUSINESS UNIT - Aditya, Rizky; Soemitra, Andri; Arif, Muhammad (Moneter: Jurnal Keuangan dan Perbankan, 2023)
This study aims to examine the critical points of sharia compliance with Murabahah financing products for motorbikes to State Civil Apparatuses (ASN) in the pre offering letter program at PT Bank SUMUT Sharia Business Unit at the time of pre-contract, during the contract and after the contract. This type of research is descriptive qualitative research. The research results show that. The critical point of sharia compliance with murabaha financing products for motorbikes to the State Civil Apparatus (ASN) in the pre offering letter program at PT Bank SUMUT Sharia Business Unit when it can be emphasized that Bank Sumut Sharia Business Unit does not regulate the recording of the use of wakala contracts in the procurement of goods . When the contract is based on the principle that Bank Sumut Syariah Business Unit as the facilitator or seller must receive the goods from the supplier before the goods are sold to the buyer (customer) as inventory ready to be sold at acquisition cost. Then, after the contract is seen, the ownership status of the goods before being sold to the customer becomes a crucial point for deviations from murabahah contract practices . Therefore, improvements should be made to the practice flow of murabahah financing contracts with the main objective of securing sharia principles in terms of possession of goods, including the required documents. Bearing in mind, this is the critical point for the occurrence of slight deviations/confusion in the practice of murabahah contracts .